2020
DOI: 10.21203/rs.3.rs-36111/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

­­­­­­Genomic analysis of worldwide sheep breeds reveals PDGFD as a major target of fat-tail selection in sheep

Abstract: Background: Fat tail is a unique trait in sheep acquired during domestication. Several genomic analyses have been conducted in sheep breeds from limited geographic origins to identify the genetic factors underlying this trait. Nevertheless, these studies obtained different candidates. The results of these regional studies were easily biased by the breed structures. Results: To minimize the bias and distinguish the true candidates, we used an extended data set of 968 sheep representing 18 fat-tailed breeds and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Moreover, studies have shown that the lack of ENPP2 has a signi cant protective effect on hepatic steatosis [21]. Dong et al [22] found that the expression of PDGFD in adipose tissue of obese individuals was higher than that of lean individuals. In this study, PDGFD was also highly expressed in BMECs with high MFP meanwhile, the downregulated gene KCNMA1 also showed a downregulated trend in white adipose tissue and hypertrophied adipocytes of mice on the high-fat diet [23], which con rmed the reliability of sequencing, suggesting that PDGFD and KCNMA1 genes may play an important role in milk fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies have shown that the lack of ENPP2 has a signi cant protective effect on hepatic steatosis [21]. Dong et al [22] found that the expression of PDGFD in adipose tissue of obese individuals was higher than that of lean individuals. In this study, PDGFD was also highly expressed in BMECs with high MFP meanwhile, the downregulated gene KCNMA1 also showed a downregulated trend in white adipose tissue and hypertrophied adipocytes of mice on the high-fat diet [23], which con rmed the reliability of sequencing, suggesting that PDGFD and KCNMA1 genes may play an important role in milk fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The target genes expression trends are consistent with the DELs that may be targeted and regulated, which is consistent with the general mode of action of lncRNAs on genes [34], and further re ects the accuracy of the sequencing results. It is worth noting that FABP4 is a gene encoding a highly rich fatty acid-binding proteins in the mammary gland, which may have a targeting relationship with TCONS _00082721 and TCONS _00172817 [22]. Among all lncRNAs related to lipid metabolism, TCONS_00082721, TCONS_00119434, TCONS_00191498, TCONS_00007612, TCONS_00118412, and TCONS_00163391 are long intervening/intergenic noncoding RNAs (lincRNAs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hair fibres were examined using scanning electron and light microscopes at USTEM, TU Wien and Austrian Archaeological Institute, respectively. We assessed 51 SNPs in the PDGFD gene associated with the derived fat-tail phenotype [18], using the genotype calls of modern fat and thin-tailed breeds to define the derived allele [43,44]. As the average genome coverage was too low for accurate diploid genotype calls, we report base calls for both alleles.…”
Section: Methodsmentioning
confidence: 99%
“…This enables characterization of the mummy skin metagenome and population genomic profiling of this sheep in the context of modern breeds. We also genotype 51 SNPs within the first intron of the platelet-derived growth factor D ( PDGFD ) that are highly differentiated between fat-tailed and thin-tailed breeds [18]. Finally we genotype the antisense EIF2S2 retrogene insertion within the 3′ UTR of the IRF2BP2 gene that influences the woolly phenotype and is derived relative to the ancestral coarse ‘hairy’ coat [19], in tandem with fibre analysis using scanning electron microscopy (SEM).…”
Section: Introductionmentioning
confidence: 99%